An investigation into linguistic features of collective nouns in English and Vietnamese short stories - Bùi Thị Vy Thuyền (Trường Đại học Ngoại ngữ, Đại học Đà Nẵng, 2024)
The study focuses on finding out the cohesive and semantic features of collective nouns in English and Vietnamese short stories for the purpose of implication in teaching and learning English. The data for the study is collected from English and Vietnamese short stories. The study is carried out through the adoption of descriptive, analytic, qualitative, quantitative, and contrastive approaches. In the finding and discussion, in terms of cohesive features of collective nouns, we have discussed the lexical cohesiveness of collective nouns in both languages in the light of the theories of Halliday and Hasan (1994) and John Flowerdew (2013). With respect to semantic features, many different types of collective nouns such as collective nouns for people, things, and animals are analyzed and argued. Simultaneously, the similarities and the differences between English and Vietnamese collective nouns in terms of lexical cohesion as well as semantic features are also emphasized. It is hoped that the findings of the research will make a certain contribution to teaching and learning discourse analysis in general and collective nouns in particular.